PEWARNAAN GRAF PADA PETA WILAYAH KOTA SEMARANG DENGAN ALGORITMA GREEDY - Ade Ima Afifa Himayati; Erik Maurten Firdaus; Findasari Findasari (Universitas Muhammadiyah Kudus, 2023)
The coloring of the sub-districts in the city of Semarang can be optimized using the Greedy algorithm. Districts are assumed to be points and lines to connect two adjacent areas. Greedy Algorithm is a form of algorithm that has been developed to solve the problem of graph coloring so that it produces minimal colors that must be used without any bordering areas using the same color. Greedy's algorithm uses a set of color candidates and initialization of the solution is made. Staining is done at the first point with the greatest degree. Furthermore, the appropriateness of the color is checked with the principle that no neighboring points have the same color. The resulting colors are members of the solution set. The coloring process is repeated so that all points are colored. Regional coloring in the city of Semarang with the Greedy algorithm resulted in 4 colors as the minimum color solution used to color all sub-districts in the city of Semarang